In vitro Evaluation of the Marginal Fit and Internal Adaptation of Zirconia and Lithium Disilicate Single Crowns: Micro-CT Comparison Between Different Manufacturing Procedures - Riccitiello, Francesco (Open Dent J, 2018)
BACKGROUND: Prosthetic precision can be affected by several variables, such as restorative materials, manufacturing procedures, framework design, cementation techniques and aging. Marginal adaptation is critical for long-term longevity and clinical success of dental restorations. Marginal misfit may lead to cement exposure to oral fluids, resulting in microleakage and cement dissolution. As a consequence, marginal discrepancies enhance percolation of bacteria, food and oral debris, potentially causing secondary caries, endodontic inflammation and periodontal disease. OBJECTIVE: The aim of the present in vitro study was to evaluate the marginal and internal adaptation of zirconia and lithium disilicate single crowns, produced with different manufacturing procedures. METHODS: Forty-five intact human maxillary premolars were prepared for single crowns by means of standardized preparations. All-ceramic crowns were fabricated with either CAD-CAM or heat-pressing procedures (CAD-CAM zirconia, CAD-CAM lithium disilicate, heat-pressed lithium disilicate) and cemented onto the teeth with a universal resin cement. Non-destructive micro-CT scanning was used to achieve the marginal and internal gaps in the coronal and sagittal planes; then, precision of fit measurements were calculated in a dedicated software and the results were statistically analyzed. RESULTS: The heat-pressed lithium disilicate crowns were significantly less accurate at the prosthetic margins (p<0.05) while they performed better at the occlusal surface (p<0.05). No significant differences were noticed between CAD-CAM zirconia and lithium disilicate crowns (p>0.05); nevertheless CAD-CAM zirconia copings presented the best marginal fit among the experimental groups. As to the thickness of the cement layer, reduced amounts of luting agent were noticed at the finishing line, whereas a thicker layer was reported at the occlusal level. CONCLUSION: Within the limitations of the present in vitro investigation, the following conclusions can be drawn: the recorded marginal gaps were within the clinical acceptability irrespective of both the restorative material and the manufacturing procedures; the CAD-CAM processing techniques for both zirconia and lithium disilicate produced more consistent marginal gaps than the heat-pressing procedures; the tested universal resin cement can be safely used with both restorative materials.